Evaluation of cytogenetic damage induced by antihypertensive drug Amlodipine: in vitro - Sayran Salih; Rawaa Abdo; Dian Salih; Asaad Alasady (المجلة العراقية للصيدلة, 2022)
Background: Amlodipine is a calcium channel blocker medication used to treat high blood pressure and coronary artery diseases for long term of use. Sufficient studies reporting the cytogenetic effects of this drug have not reporting yet. Aim of study: This study aimed to assess the frequency of chromosomal aberrations of amlodipine on human blood lymphocytes in vitro. Material and Methods: In this study, the in vitro genotoxic effects of amlodipine have been determined in human peripheral blood lymphocytes by using chromosomal aberrations: 0; 5; 10; 15; 25 and 50mg/mL concentrations of amlodipine was used. All samples cultured in 37°C incubation for 72 hours. Then treated with Colcemid. Results: Amlodipine did not appear to have cytogenetic effects in vitro, as no significant increases in the frequency of chromosomal aberrations were found in cultures treated with different concentrations compared to cultures treated with the recommended concentration (10 mg/mL). The highest concentrations (50 mg/mL) of amlodipine increased chromosomal aberrations compared to negative control, but these increases were not statistically significant Conclusion: Amlodipine is not seemed to be genotoxic active ingredients in human lymphocytes in vitro.